Olanzapine versus Aprepitant for Prophylaxis of Nausea and Vomiting in Patients Receiving Highly Emetogenic Chemotherapy: A Prospective Randomized Study - Gedela, Lakshmi D.; Chennamaneni, Rachana; Lakshmi, Konatam Meher; Bala, Stalin Chowdary; Gundeti, Sadashivudu (Indian Journal of Medical and Paediatric Oncology, 2025)
Chemotherapy-induced nausea and vomiting (CINV) negatively affects health-related quality of life and performance status in patients undergoing chemotherapy. Aprepitant, palonosetron, and steroids (APD) notably enhance the rates of complete response (CR) in patients receiving highly emetogenic chemotherapy (HEC). This study compares the efficacy, cost, and quality of life between APD and olanzapine, palonosetron, and dexamethasone (OPD).The main aim of the study was to evaluate the control of CINV by measuring CR and total control (TC). The secondary aim was to examine the impact of CINV on patients' quality of life.This is a prospective randomized study of patients newly diagnosed with malignancy, aged > 18 years. This analysis was done over a period of 1 year in patients receiving HEC. All patients eligible for the study are randomized to APD versus OPD regimen. Stratification was done according to the chemotherapy regimen used. Quality of life, the secondary objective, was assessed by using the Functional Living Index-Emesis.Overall, 120 patients were randomized during the study period to both the arms at 1:1 ratio. Baseline characteristics were equally matched between both the arms. Both the arms showed effective prevention of vomiting in nearly 80% of the study population. Emesis was reported in 19% of APD and 20% in the OPD arm (p = 0.75). Grade 3/4 vomiting was not seen in any patient in the olanzapine group. The CR rates in all patients are 75 and 77% with APD and OPD arms, respectively (p = 0.83). Overall, the TC of CINV is similar among the two groups, 57 and 60% in APD and OPD, respectively (p = 0.85). Delayed nausea was significantly lower in the OPD arm compared with APD (17% vs. 38%, respectively, p = 0.025). In patients receiving anthracycline plus cyclophosphamide chemotherapy, OPD outperformed APD in delayed nausea and delayed TC (p = 0.002 and 0.015, respectively). Both drugs were effective in maintaining a good quality of life and no significant difference was observed among both the groups. The most common toxicity observed in both the arms was anorexia.Both regimens had similar efficacy in preventing CINV, with no significant differences in CR and TC rates. Olanzapine was more effective for delayed nausea than aprepitant, suggesting it is a cost-efficient alternative for managing CINV in HEC patients.
Keywords: aprepitant; olanzapine; highly emetogenic chemotherapy; nausea and vomiting